Membrane-targeting AM-0016 kills mycobacterial persisters and shows low propensity for resistance development. (May 2016) - Mukherjee, Devika; Zou, Hanxun; Liu, Shouping; Beuerman, Roger; Dick, Thomas
Aim: To test the hypothesis that targeting the cytoplasmic membrane may be an effective way to kill persister mycobacteria and delay the emergence of resistance.Methods:   In vitro activity of AM-0016, a novel xanthone-based antibacterial, was assessed against growing and persister tubercle bacilli. Resistance mutation frequencies were determined. Biochemical membrane and electron microscopic analyses were carried out.Results: AM-0016 rapidly sterilized growing tubercle bacillus cultures and displayed strong bactericidal activity against persister bacteria. Spontaneous resistance mutation frequency was lower than 10 -8 . Exposure to AM-0016 resulted in rapid collapse of the membrane potential. Imaging revealed deformation of the cell envelope.Conclusion: Targeting the cytoplasmic membrane may be an attractive approach to eliminate persister mycobacteria and slow down the emergence of genetic drug resistance.